Long-lasting effect of NMDA receptor antagonist memantine on ethanol-cue association and relapse - Vengeliene, Valentina; Olevska, Anastasia; Spanagel, Rainer (Journal of neurochemistry, 2015)
It is well known that the glutamatergic system plays a crucial role in alcohol addiction and especially in relapse-like behaviour. However, results of clinical studies on compounds that influence the activity of the glutamatergic system have been disappointing so far. The aim of our study was to establish treatment conditions under which the N-methyl-d-aspartate receptor (NMDAR) antagonist memantine may produce more reliable treatment effect with respect to alcohol relapse-like behaviour. For this purpose, male Wistar rats were trained to associate several discrete stimuli with ethanol delivery. Thereafter, half of the animals received a brief memory reactivation session followed by two administrations of 20 mg/kg of memantine, while the other half received the same treatment without memory reactivation. Afterwards, a cue-induced ethanol-seeking behaviour test was performed followed by repeated extinction sessions and a reacquisition test. Our data show that administration of memantine reduced responding on the ethanol-associated lever in a cue-induced ethanol-seeking test. This reduction did not depend on whether or not a memory reactivation session was introduced prior to memantine administration. Following extinction, however, reacquisition of ethanol self-administration was only impaired in the group where memantine was given after a short memory reactivation session, showing that this schedule of drug administration produced a long-lasting disruption of the association between the conditioned stimuli and the delivery of ethanol. In conclusion, we show that memantine disrupted the drug-cue association, which consequently interfered with relapse-like behaviour supporting the possibility that memantine is a treatment option for alcoholism. Our data supports the possibility that memantine is a treatment option for alcoholism. However, the effectiveness of this drug seems to lie in its ability to disrupt conditioned behaviours and should be given in conjunction with exposure to conditioned drug stimuli.